Schumpeter's price theory - Bloch, Harry (The History of Economic Thought Society of Australia, 2009)
Schumpeter distinguishes between the circular flow of economic activity and economic development. The former is characterised by equilibrium, while the latter involves discontinuous change. The price theory that Schumpeter associates with the circular flow is the well established Walrasian price system. However, the price theory which Schumpeter proposes for economic development is only partially developed in writings and has been largely ignored since. Yet, it is the analysis of economic development that constitutes Schumpeter's enduring contribution to economic thought. This paper provides a critical examination of Schumpeter's price theory as it applies when there is economic development.